AB0555 ANTI-RO POSITIVITY EFFECT ON CLINICAL CHARACTERISTICS AND MORTALITY IN A SINGLE-CENTER COHORT OF ANTISYNTHETASE SYNDROME PATIENTS. (2nd June 2020) - Bozzalla Cassione, E.; Biglia, A.; Zanframundo, G.; Grignaschi, S.; De Stefano, L.; Delvino, P.; Marasco, E.; Montecucco, C.; Cavagna, L.
Abstract : Background: Antisynthetase syndrome (ASSD) is an heterogeneous disease characterized by the occurrence of anti-synthetase antibodies (ARS) and the classic triad of arthritis, myositis and Interstitial Lung Disease (ILD). Pulmonary involvment bears an increased risk of life threatening events, being the main cause of mortality in these patients. No significant differences in mortality have been noticed among the different ARS specificities. However the role of extractable nuclear antigen antibodies on mortality in these patients is still matter of debate. Objectives: To asses the effect of anti-RO antibodies on clinical characteristics and mortality in a large italian single-center cohort of ASSD patients. Methods: Cohort study of outcome, clinical and laboratory characteristics, at baseline and at last follow-up, of 55 ASSD patients progressively enrolled and followed-up at our out-patient clinic. Survival was estimated with Kaplan-Meier function and comparison between frequencies of clinical characteristics was studied with Chi-square test. Results: We identified 30 anti-Ro+ (M:F=1:4) and 25 anti-Ro- (M:F=1.5:1) ASSD patients. No difference in the age of onset was observed (p value=0.83). Classic triad prevalence and evolution was similar between the two groups with only significant difference of ILD prevalence at last follow up, higher in anti-Ro+ patients group (p value=0.01). Overall mortality was of 13 subjects (23%) during the follow-up period (median 53 months, IQR 16-114). Despite the significantly higher pulmonary involvment in the anti-Ro+ group no difference between mortality in anti-Ro positive and negative groups was observed. Adjusting mortality to include disease-related events only did not provide any additional difference (p value=0.5) (Table 1 ). Survival curves of the two groups were not different at any time point (Log-rank test, p value 0.98) (Figure 1 ). Conclusion: The clinical spectrum and the time course of ASSD is not significantly affected by the presence of anti-Ro antibodies, althuough ILD seems to be more associated to anti-Ro antibodies. Despite higher prevalence of ILD in Ro positive group no difference in mortality was observed in respect to anti-Ro negative patients. References: [1]Cavagna L. Medicine (Baltimore) 2015 Aug;94(32):e1144 [2]Marie I. Semin Arthritis Rheum. 2012 Jun;41(6):890-9 Disclosure of Interests: None declared